Association of metalloestrogens exposure with depression in women across reproductive lifespan - Ren, Junjie; Wu, Wanxin; Li, Jia; Hu, Qifang; Zhang, Mi; Wang, Jing; Li, Xiaoming; Li, Yanwen; Huang, Binbin (Frontiers in Psychiatry, 2024)
BackgroundExposure to metal could impact women’s depression risk. However, the connection and mechanisms between metalloestrogens exposure and depression are still not fully understood. We aim to explore the associations between metalloestrogens and the risk of depression in women across reproductive lifespan.MethodsUsing data from NHANES 2011-2018, we employed logistic regression and baknernel machine regression (BKMR) to study links between metalloestrogen exposure and depression in US women. We analyzed how contraceptive use affects this relationship.ResultsThe study involved 3,374 adult women, with 345 of them experiencing depression. Our research revealed that certain metalloestrogens like Ba, Ca, Pb, Sb, and Sn were linked to higher depression risk in women, while Hg was associated with lower depression risk in older women. For women aged 18-44, a blend of metalloestrogens showed a significant positive correlation with depression risk, and the likelihood of depression in later years notably rose when the metal mixture concentration reached or exceeded the 60th percentile. Oral contraceptives would have an effect on the impact of metalloestrogen mixture exposure on depression in women during the reproductive stage.ConclusionsOur study indicates a significant link between metalloestrogen exposure and a higher risk of depression in adult women in the United States. This finding can aid in identifying the connection and enhancing women’s mental well-being.